2013
DOI: 10.1017/s1742758413000192
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lambdacyhalothrin on arthropod natural enemy populations in irrigated rice fields in southern Brazil

Abstract: Abstract. The present study aimed to determine the selectivity of the pyrethroid lambdacyhalothrin on arthropod natural enemy populations in irrigated rice fields in Rio Grande do Sul, Brazil. The study was conducted at three sites: districts of Cachoeira do Sul, Eldorado do Sul and Capivari do Sul during the crop years of 2007/2008 and 2008/ 2009. Each site consisted of two subareas divided into four plots. One of the subareas received a spray application of 150 ml/ha of lambdacyhalothrin CS 50, while the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
1
4
0
1
Order By: Relevance
“…Least diversity was recorded in lambda cyhalothrin 5%EC and chlorpyriphos 20%EC treated plots. Similar trend was observed in case of evenness index and emamectin benzoate 5%SG showed the (Fritz 2013). In the present study, the spider population was more in sulfoxaflor 25%SC followed by pymetrozine 50%WG and emamectin benzoate 5%EC.…”
Section: Resultssupporting
confidence: 84%
“…Least diversity was recorded in lambda cyhalothrin 5%EC and chlorpyriphos 20%EC treated plots. Similar trend was observed in case of evenness index and emamectin benzoate 5%SG showed the (Fritz 2013). In the present study, the spider population was more in sulfoxaflor 25%SC followed by pymetrozine 50%WG and emamectin benzoate 5%EC.…”
Section: Resultssupporting
confidence: 84%
“…7 Among them are the pyrethroid insecticides, which may affect spider survival, 8,9 feeding behavior 9,10 and locomotor activity, 11 even at concentrations below the recommended field dose. One widespread pyrethroid insecticide is lambda-cyhalothrin, which is known to reduce the abundance and diversity of natural enemies, including spiders, in field scenarios 12,13 and to cause spider mortality under laboratory conditions. 8 Moreover, lambda-cyhalothrin is cataloged as a bioaccumulative and toxic substance for non-target organisms, and is currently classified as a candidate for substitution in the EU.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were obtained by Sechser et al (2003), Seal et al (2006) and Khani et al (2012) with imidacloprid proved to be harmful to coccinellids. Karthikeyan et al (2008), Fritz et al (2013) and Rodrigues et al (2013) observed that spiders were significantly reduced with lambda cyhalothrin was sprayed in rice. Sasikumar and Kumar (2012) also observed that the spiders are reduced with foliar application of lambda cyhalothrin and imidacloprid in sesame crop and Sherawat et al (2015) with imidacloprid on spiders in Pakistan.…”
Section: Resultsmentioning
confidence: 99%